Molecular phylogeny and morphological characterization of the etiological agent of sour rot on fruits and vegetables in Brazil - Paes, Simone Albino (2020)
Sour rot represents a serious problem in the field and postharvest of fruits and vegetables by limiting production and marketing. Geotrichum candidum has been reported as the main species causing this disease. In this study, 165 fungal isolates causing postharvest rot in different states of Brazil were characterized on the basis of molecular phylogeny and morphology. For molecular characterization, the genomic DNA was extracted, the D1/D2 domain of large subunit rRNA (LSU) gene was amplified and sequenced. The phylogenetic analyses revealed that 129 isolates of this study grouped with the species Geotrichum candidum, while other isolates did not cluster to any known species, probably representing new species. Moreover, other fungal genera, i.e. Hyphopichia, Magnusiomyces, Saccharomycopsis, Trichosporon and Zygoascus were identified associated with the sour rot disease on fruits and vegetables in Brazil. All species tested, including the putative new species, were pathogenic when artificially inoculated on healthy tomato fruit types, Long-self life, Italian tomato and sweet grape, as well as potato tubers and red mombin fruits. In conclusion, although Geotrichum candidum has been related as the only species causing sour rot, other species of Geotrichum and other genera are associated with sour rot on fruits and vegetables in Brazil, which demonstrates a diversity of fungi associated with this disease. Keywords: Dipodascaceae. Geotrichum . Postharvest disease. Rot disease.